Acromicric dysplasia and hearing loss: A case report - Pinto, Ana Nóbrega (2018)
Introduction: Acromicric dysplasia is an extremely rare autosomal dominant bone dysplasia characterized by progressive growth retardation, short hands and feet, mild facial dysmorphism and generalized joint limitation. Association with ear, nose and pharyngolaryngeal alterations has been previously reported. However, little is known about the otolaryngologic aspects that may accompany this disease. We pretend to raise awareness to the otolaryngologic aspects that may accompany acromicric dysplasia and to the possible interventions that improve these patients quality of life. Clinical Case: We present the case of a ten-year-old girl referred to the otorhinolaryngology consultation with complaints of progressive hearing loss. Hearing evaluation confirmed bilateral severe mixed hearing loss and the patient was successfully rehabilitated with bone-anchored hearing aids. Discussion/Conclusions: Evaluation by an otolaryngologist should be part of the management of children with bone dysplasias, especially if they present with associated symptoms, to allow an early diagnosis and proper intervention.